Rosacea fulminans: unusual clinical presentation of rosacea - Jessica Castiel Coutinho; Danielle Cristine Westphal; Laís Cruz Lobato; Antônio Pedro Mendes Schettini; Mônica Santos (Sociedade Brasileira de Dermatologia, 2016)
Abstract Rosacea fulminans or pyoderma faciale is a rare cutaneous disorder that usually affects women usually between the ages of 15-46. The disease is characterized by sudden onset of papules, pustules, cysts, and painful coalescing nodules with red-cyanotic centrofacial erythema. Although its etiology remains unknown, hormonal, immunological, and vascular factors have been reported. Early diagnosis and prompt treatment should minimize unsightly scars. We report a case of a 33-year-old female patient treated with traditional doses of doxycycline, with improvement of the lesions and regression of the condition in two months.